Not all firms are created equal: SMEs and vocational training in the UK, Italy, and Germany - Chiara Benassi; Niccolo Durazzi; Johann Fortwengel (Max Planck Institute for the Study of Societies, 2020)
Why do skill formation systems put SMEs at greater disadvantage in some countries than others vis-à-vis large employers? By comparing vocational education and training (VET) institutions and their differential effect on firms of different sizes across three countries (UK, Italy, and Germany), we show that the design of VET has profound implications for shaping the ability of SMEs to use institutions as resources. In particular, quasi-market institutions in the UK amplify SMEs' disadvantage, while non-market coordinating institutions in Italy and Germany narrow the gap between SMEs and large employers. By unpacking the comparative disadvantage of SMEs, we offer important nuances to the argument that institutions help firms coordinate their business activities in different varieties of capitalism. – – Warum erfahren kleine und mittelständische Unternehmen (KMU) durch Berufsbildungssysteme mehr Nachteile als große Unternehmen und warum ist dieser Unterschied in manchen Ländern größer als in anderen? Wir vergleichen Ausbildungsinstitutionen und ihren unterschiedlichen Effekt auf Firmen verschiedener Größe in drei Ländern (Großbritannien, Italien und Deutschland). Dabei zeigen wir, dass die Art der Institutionen die Möglichkeit von Firmen, die vorhandenen Institutionen als Ressource zu nutzen, beeinflusst. Insbesondere verstärken die in Großbritannien vorherrschenden quasimarktlichen Institutionen den Nachteil von KMU, wohingegen nichtmarktliche Institutionen in Italien und Deutschland den Unterschied zu großen Unternehmen verringern. Durch das Aufzeigen des komparativen Nachteils von KMU leistet unser Papier einen Beitrag zu einer nuancierteren Sichtweise der Rolle von Institutionen in verschiedenen Spielarten des Kapitalismus.
hdl:21.11116/0000-0006-3A9A-C
Keywords: 300; comparative political economy; firm size; small and medium-sized enterprises (SMEs); varieties of capitalism; vocational education and training (VET); Berufsbildung; kleine und mittlere Unternehmen (KMU); Spielarten des Kapitalismus; UnternehmensgröØe; Vergleichende Politische Ökonomie